Pengaruh Motivasi Kerja, Lingkungan Kerja Dan Budaya Kerja Terhadap Kinerja Karyawan - Widi, Widianto; Sonny Hersona; Banuara Nadaek; DJ Suyaman (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
Quality human resources will be able to show good performance achievements. Several performance factors can be seen from motivation, work environment, work culture and so on. This needs to be taken into account by companies including Machine and Machine Tool Industrial Companies for Metal Working in the International Industrial City (KIIC) Area. The purpose of this study is to determine and analyze the influence of motivation, work environment, work culture on employee performance. The research method used is through a quantitative approach with the analytical method used is path analysis. Simple random sampling is a sampling technique used, where the sample used is 82 out of a population of 116 people. The results showed that partially work motivation has a significant positive effect on performance by 13.96%, the work environment has a significant positive effect on performance by 19.97% and work culture has a significant positive effect on performance by 32.50%. The conclusion obtained in this study is that work motivation, work environment and work culture simultaneously have a significant and positive effect on performance by 67.50%. Because work motivation, work environment and work culture are inseparable parts of improving performance.